Application and effect of developmental supportive care on growth and neurobehavioral development in preterm infants - Niu, Xiaoqing; Li, Ling; Jing, Yachao (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the effects of developmental supportive care on growth, neurobehavioral function, and cognitive development in preterm infants.MethodsIn this retrospective study, a total of 104 preterm infants born in our hospital were enrolled and divided into the routine care group (n = 49) and the developmental supportive care group (n = 55) based on the nursing approach they received during their hospitalization. Both groups received nursing care during hospitalization for 7 days. Routine care included monitoring of vital signs, feeding management, environmental control, skin and oral care, positioning, management of clinical conditions, and parental education. Developmental supportive care was implemented on the basis of routine care and comprised individualized care plans, environmental and sensory regulation, clustered care, tactile stimulation, non-nutritive sucking training, kangaroo care, feeding optimization, pain and stress management, parental involvement, and systematic recording and evaluation of the care effects. Outcome measures included body weight, length, head circumference, and chest circumference before and after the care; neurobehavioral function (passive muscle tone, active muscle tone, primitive reflexes, behavioral state, and general status); and cognitive development assessed by the Mental Development Index (MDI) and Psychomotor Development Index (PDI).ResultsThere were no statistically significant differences between the two groups in baseline characteristics, growth indices, neurobehavioral function, or cognitive development before the care (P > 0.05). After the care, growth parameters increased in both groups, with body weight, length, head circumference, and chest circumference significantly higher in the developmental supportive care group than in the routine care group (P < 0.05). Neurobehavioral scores as well as MDI and PDI scores improved in both groups, with significantly greater improvements observed in the developmental supportive care group (P < 0.05).ConclusionsDevelopmental supportive care can effectively promote growth, neurobehavioral function, and cognitive development in preterm infants. Compared with routine care, this model offers systematic and individualized nursing approaches that enhance physiological stability and developmental outcomes, providing reliable evidence for clinical neonatal nursing practice.